2017
DOI: 10.1002/dc.23679
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of the papillary thyroid carcinoma with a solid component: A cytological and clinical correlation

Abstract: PTCSC may pre-operatively be identified by detecting its characteristic cytological features in FNA smears, regardless of the proportion of SC within the tumor. Because clinical outcomes of PTCSC remain undetermined, it is imperative to postulate PTCSC as a differential diagnosis, even when classical nuclear features of PTC are present. Diagn. Cytopathol. 2017;45:391-398. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…Although we found nuclear elongation in most (89%) of our cases, Baloch et al [24] reported nuclei in SVPTC to be more rounded than oval. INIs were found in 67% of the cases in the current study, not very different from the results reported by Higuchi et al [12] (78%) and Ohashi et al [18] (65%). INIs, as expected, were also seen in most (83%) of cPTCs.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…Although we found nuclear elongation in most (89%) of our cases, Baloch et al [24] reported nuclei in SVPTC to be more rounded than oval. INIs were found in 67% of the cases in the current study, not very different from the results reported by Higuchi et al [12] (78%) and Ohashi et al [18] (65%). INIs, as expected, were also seen in most (83%) of cPTCs.…”
Section: Discussioncontrasting
confidence: 47%
“…In the current study, SVPTC constituted 2.8% of the total PTC cases. Conventionally, it has been associated with childhood presentation, prior radiation exposure, and a less favorable prognosis than cPTC [17, 18]. However, a few authors have reported these tumors to have age and prognosis comparable to cPTC and no association with radiation exposure [4, 5, 18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations